ANTECEDENTS EMPLOYEE PERFORMANCE: A PERSPECTIVE REINFORCEMENT THEORY - Susanto, Susanto; Lim, Benny; Linda, Tina; Tarigan, Sri Aprianti; Wijaya, Elyzabeth (Journal of Industrial Engineering & Management Research, 2021)
The power of praise in the workplace can move employees from apathy or resentment to happiness and productivity. Reinforcement such as positive reinforcement makes people feel appreciated and encouraged, which can be motivating and rewarding. In this research, the writer researches IEC Malaka Medan that locates at Jalan Malaka no 29/59 Medan. IEC (International Education Centre) was the well-known image in English Education Centre. In conducting the research, the writer uses a questionnaire containing ten questions, with each question having five answers to be chosen, distributed to 30 respondents. The questions are designed by using interval data which uses a Likert Scale rating. For analyzing the collected data, the writer will use statistical formulas, which are correlation formulas for test whether it is valid. Cronbach's Alpha for testing reliability, Pearson's product moment for correlation test, normality test to identify whether the data is normal, determination formula and linear regression for identifying relationship between variables and z-test for hypothesis test. In analyzing data, the writer used some methods such as the validity test, the reliability test, the statistical data, the normality test, the correlation test, the determination test, the linear regression test, and the hypothesis test. The percentage of reinforcement towards employees' performance is 49.7% and the remaining 50.3% is impacted by other factors. The coefficient correlation between variable x and variable y resulted in 0.705, which means that there is a relationship between reinforcement and employees' performance at IEC Malaka Medan. Keywords: Reinforcement, Employees Performance